RANCANG BANGUN ALAT PERAGA IPA TERPADU SMP KELAS VII PADA MATERI GLOBAL WARMING DALAM IMPLEMENTASI KURIKULUM 2013 - Eko Retno Mulyaningrum; Siti Patonah; Duwi Nuvitalia (Universitas PGRI Semarang, 2014)
Abstract: The objective of this study is to develop the teaching aids of science subjects required, based on kurikulum 2013 at seven grade students in global warming material. In this study, it will be developed the teaching aids of science to support the implementation of kurikulum 2013. This is because of the teaching aids of science is one of supporting the learning effectiveness. Moreover of kurikulum 2013, the writer looked, there were not the teaching aidsof scienceavailability in learning yet. While the specific purposes are; 1) to determine the characteristic of teaching aids, 2) to determine the teaching aids validity. This study was conducted in June to August 2014. It was held in Physics Laboratory at University of PGRI Semarang. The method was mix-method design. The quantitative analysis has done statistically to determine the experts?óÔé¼Ôäó validation. While the qualitative analysis to the data of validation sheet, interview, observation and other qualitative data. Based on the study result, the conclusion is the teaching aids design of integrated natural science of seven grade students at global warning material was obtained the teaching aids appropriate to the valid minimal criteria, based on the analysis by physicist, biologist and chemist. The average of validator evaluation was obtained a perfectly valid criterion, making it feasible to use in learning.Key words: Teaching Aids, Integrated Natural Science, Global Warming